The Effect of the Amount of Charge on the Force and the Direction of the Force on Coulomb's Law Using Phet Simulation - Auliya, Misykah; Hilma Nurul Fajrin; Muhammad Fikri Assiddiqi (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2022)
This experiment aims to determine the effect of the magnitude of the charge on the direction of the force generated. Data collection was carried out using the PhET Simulation Coulomb's Law. The method used in conducting research is a combination research method. The results of the research found that the amount of charge given will affect the direction of the force generated. This is important so that there are no misunderstandings in understanding the concept of the material.